Analisis umur perusahaan, keragaman gender, kesulitan keuangan, tipe industri dan dewan komisaris independen terhadap pengungkapan laporan keberlanjutan - Hepata, Indra; Suwasono, Heru (Journal of Accounting and Digital Finance, 2024)
This study aims to determine the effect of Company Age, Gender Diversity, Financial Distress, type of industry and Independent Board of Commissioners on sustainability reports in State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This type of research is quantitative, and the data used is secondary. The population used in this study were BUMN companies listed on the Indonesia Stock Exchange in 2019-2023, with a sample size of 24 companies. The sampling technique used was purposive sampling. The analysis method used was multiple linear regression analysis. The results of this study indicate that company age, gender diversity, financial distress, industry type, and independent board of commissioners simultaneously affect sustainability reports. Partially, financial distress hurts sustainability reports; company age positively affects sustainability reports, and gender diversity, type of industry and independent board of commissioners do not affect sustainability reports.